Bending behaviour of Textile Reinforced Concrete sandwich beams. (1st October 2015) - Colombo, Isabella Giorgia; Colombo, Matteo; di Prisco, Marco
Highlights: The large shear deformability of EPS governs the sandwich global response. The solution investigated behaves as a partially composite sandwich. Sandwich beam experiences large ductility thanks to EPS compressive plastic strain. Fabric position in the thickness of the TRC layer affects multicracking pattern. Abstract: A prefabricated concrete sandwich panel, with insulating material acting as a structural layer able to transfer the shear stresses, is discussed. The use of an in-pressure casting technique allows to avoid the use of glue and to prevent the debonding between the layers thanks to the good bond obtained during the production. Sandwich beams characterized by a thick internal expanded polystyrene foam core and by two thin external Alkali-Resistant glass Textile Reinforced Concrete layers are experimentally investigated according to four point bending scheme. The significant role played by the tangential non linear behaviour of the EPS foam is shown.